2013
DOI: 10.1074/mcp.m112.026633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of O-Linked N-Acetylglucosamine (O-GlcNAc)-modified Osteoblast Proteins by Electron Transfer Dissociation Tandem Mass Spectrometry Reveals Proteins Critical for Bone Formation

Abstract: (3), O-GlcNAc modification is now appreciated as a nutrient-responsive mechanism for modulating signal transduction (4, 5) and transcriptional regulation (6, 7). In contrast to N-and O-linked glycosylation taking place in the endoplasmic reticulum and Golgi apparatus, reversible O-GlcNAcylation occurs in the cytoplasm and nucleus and is catalyzed by O-GlcNAc transferase (OGT), which transfers GlcNAc from UDP-GlcNAc to Ser/Thr residues, and O-GlcNAcase (OGA), which removes it. These highly conserved enzymes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 87 publications
3
62
0
Order By: Relevance
“…3B, the chitosan microspheres dissolved and the sample formed a porous surface. Studies have found that the chitosan degradation product, N-acetyl glucosamine, could promote osteoblast activity, hematoma and fibrous callus formation, and significantly shorten the healing time of bone defects [33]. Gregoire et al thought the reason for these outcomes was that Nacetyl glucosamine could promote osteoblast activity and increase bone morphogenetic protein expression in the bone defects [34].…”
Section: Discussionmentioning
confidence: 99%
“…3B, the chitosan microspheres dissolved and the sample formed a porous surface. Studies have found that the chitosan degradation product, N-acetyl glucosamine, could promote osteoblast activity, hematoma and fibrous callus formation, and significantly shorten the healing time of bone defects [33]. Gregoire et al thought the reason for these outcomes was that Nacetyl glucosamine could promote osteoblast activity and increase bone morphogenetic protein expression in the bone defects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry has been successfully used to identify even labile protein modifications, including protein phosphorylation 12 , and O-GlcNAc modifications 34 , as well as identifying chemical modifications including covalent labeling for protein surface mapping 56 , crosslinking 78 , deamidation of asparagine 910 , and protein oxidation 1112 . In all of these systems, the amount of modification that occurs at each amino acid of a peptide or protein can have serious consequences to the interpretation of the data, whether for understanding chemical or enzymatic modification mechanisms and consequences 1316 or for interpreting data from covalent labeling or chemical cross-linking studies 7, 1720 .…”
Section: Introductionmentioning
confidence: 99%
“…During osteogenesis in mouse MC3T3-E1 cells, differentiation from preosteoblasts to osteoblasts gives rise to a global increase in the level of OGlcNAc modification (Kim et al, 2007). The activity of Runx2, a critical transcription factor for osteogenesis, was shown to be regulated by O-GlcNAc modification using the reporter assay system (Nagel and Ball, 2014;Nagel et al, 2013). In addition to osteogenesis, mouse 3T3-L1 preadipocytes also exhibit a drastic increase in global OGlcNAc levels during adipogenesis (Ishihara et al, 2010).…”
Section: O-glcnacylation Enzymes In the Nucleus Cytosol And Mitochomentioning
confidence: 99%